Variations of the abductor pollicis longus tendon and its insertion in the Thai population: Cadaveric study with clinical relevance - Vilai Chentanez; Krittameth Pasiphol; Sithiporn Agthong; Napatpong Thamrongskulsiri; Sirikorn Dokthien; Thanasil Huanmanop; Tanat Tabtieang (Translational Research in Anatomy)
Background: The abductor pollicis longus (APL) tendon exhibits significant anatomical variability, which is crucial for understanding its clinical implications in surgeries involving the thumb. While several studies have documented these variations in different populations, a systematic classification providing insights for surgical interventions targeting the thumb and its associated anatomical structures is rare. Methods: This cadaveric study involved the dissection of 87 upper extremities from 44 embalmed cadavers (22 males, 22 females). The APL tendons were meticulously dissected, and the number of tendons slips and their insertion sites were recorded. Data were analyzed using Chi-square and Fisher's exact tests to assess differences in insertion sites between sexes and sides. Results: The number of APL tendon slips distal to the first extensor compartment ranged from 1 to 5, with double slips being the most common configuration. The primary insertion site was consistently the base of the first metacarpal bone, observed in all specimens. Secondary insertion sites included the abductor pollicis brevis muscle (67.82 %), trapezium (17.24 %), opponens pollicis muscle (5.75 %), and proximal phalanx (2.30 %). Statistical analysis showed no significant differences in the insertion sites between sides and sexes. A new classification system for APL tendon slips was developed, categorizing them into three main types (Type I, II, III), and two minor types (Type IV and V), based on the number and insertion sites of the tendons. Type II with double tendon slips was the most prevalent (48.28 %). Symmetrical findings were found in 21 cases (48.84 %), with subtype IIb being the most common pattern. Conclusion: This study highlights significant anatomical variations of the APL tendon in the Thai population, with important clinical implications for surgical planning and treatment of thumb-related conditions. The proposed classification system provides a structured framework for understanding these variations, aiding in the diagnosis and surgical management.